Blends of gelatin and hyaluronic acid stratified by stereolithographic bioprinting approximate cartilaginous matrix gradients. Issue 10 (9th May 2022) - Shopperly, Lennard K.; Spinnen, Jacob; Krüger, Jan‐Philipp; Endres, Michaela; Sittinger, Michael; Lam, Tobias; Kloke, Lutz; Dehne, Tilo
Abstract: Stereolithographic bioprinting holds great promise in the quest for creating artificial, biomimetic cartilage‐like tissue. To introduce a more biomimetic approach, we examined blending and stratifying methacrylated hyaluronic acid (HAMA) and methacrylated gelatin (GelMA) bioinks to mimic the zonal structure of articular cartilage. Bioinks were suspended with porcine chondrocytes before being printed in a digital light processing approach. Homogenous constructs made from hybrid bioinks of varying polymer ratios as well as stratified constructs combining different bioink blends were cultivated over 14 days and analyzed by histochemical staining for proteoglycans/collagen type II, cartilage marker expression analysis, and for cellular viability. The stiffness of blended bioinks increased gradually with HAMA content, from 2.41 ± 0.58 kPa (5% GelMA, 0% HAMA) to 8.84 ± 0.11 kPa (0% GelMA, 2% HAMA). Cell‐laden constructs maintained vital chondrocytes and supported the formation of proteoglycans and collagen type II. Higher concentrations of GelMA resulted in increased formation of cartilaginous matrix proteins and a more premature phenotype. However, decreased matrix production in central areas of constructs was observed in higher GelMA content constructs. Biomimetically stratified constructs retained their gradient‐like structure even after ECM formation, and exclusively exhibited a significant increase in COL2A1 gene expression (+178%). Concluding, we showed the feasibility of blending and stratifying photopolymerizable, natural biopolymers by SLA bioprinting to modulate chondrocyte attributes and to create zonally segmented ECM structures, contributing to improved modeling of cartilaginous tissue for regenerative therapies or in vitro models. Abstract :